The Construction of Community Social Reality in the New Era of the Indonesian Communication System: Case Study on the Transition of Analog TV to Digital TV in Bengkulu City - Fitriansyah, M; Azara, Ustaza Kaffah (Jurnal Ilmiah Syi'ar, 2024)
Government policy through the Ministry of Communication and Information of the Republic of Indonesia, which is mandated by Law 60 A Job Creation regarding the implementation of broadcasting in accordance with current developments, is to stop analog to digital broadcasts no later than two years after the enactment of this Law. This research was carried out with the aim of examining more deeply the construction of social reality in society in the Indonesian communication system, especially in the transition from Analog TV to Digital TV. This research stems from the author's interest in examining how society views the transition from Analog TV to Digital TV. Researchers also want to know the public's views on this transition, especially in the Indonesian communication system. The subjects in this research were the Ratu Agng and Bentiring communities. This research uses qualitative methods and is analyzed using Social Construction Theory by Berger and Luckman. Determining informants in this study used a purposive sampling technique. Data collection techniques were carried out by means of observation, interviews, literature study and documentation. The results obtained from this research show that public awareness after watching information about the transition from an analog television system to a digital television system can be said to be quite good, meaning that there is awareness of the benefits of using it and concern about changing and switching to Digital TV. However, the government or KPID still needs follow-up action to help socialize it so that this matter is more easily understood by the public. Apart from that, there are challenges in the form of weak economic conditions, poor signal coverage and low understanding of technology.